A Szabad Francia Légierő tevékenysége Afrikában - Bene, Krisztián (Afrika Tanulmányok / Hungarian Journal of African Studies, 2018)
The Free French Air Forces were the air branch of the Free French Forces during the Second World War from 1940 to 1943 when they finally became part of the new regular French Air Forces. This study aims to present the activity of this special and little-known air force over the territory of Africa during this period. After the French defeat in June 1940 General Charles de Gaulle went to England to continue the fight against the Axis Forces and created the Free French Forces. Several airmen of the French Air Forces rallied to General de Gaulle which allowed the creation of the Free French Forces on 1st July 1940 under the command of Admiral Émile Muselier. The Free French commandment wanted to deploy their units during the reconquest of the French African colonies, so they were sent to participate in the occupation of French Equatorial Africa in 1940. Other flying units struggled in East and North Africa together with British troops against the invading Italian armies. These forces were reorganized in 1941 and continued the fight in the frame of fighter and bombing squadrons (groupes in French). Most of them (five of seven) were created and deployed in Africa as the Lorraine, the Alsace, the Bretagne, the Artois and the Picardie squadrons. From 1940 to 1943 5,000 men served in the ranks of the Free French Air Forces, which is a modest number if we compare with the power of the air forces of the other allied countries. At the same time, the presence and the activity of these forces were an important aid to Great Britain during a hard period of its history, so this contribution was appreciated by the British government in the end of the war at the political scene.